Data Mining and Accounting: Evolving Methods for Projecting the Financial Situation of Companies - Mhamed, Adil; Hamiche, Adil (International Journal of Business Management and Entrepreneurship, 2025)
This study examines the evolving role of data mining and artificial intelligence (AI) techniques in projecting the financial situation of companies from 1990 to 2025. Traditional accounting methods, often reliant on linear statistical models, face limitations in capturing the complexity and volatility of modern financial data. To address these challenges, this research applies both linear regression and artificial neural network (ANN) models to analyze normalized net profit data over a 35-year period. Descriptive statistics reveal moderate fluctuations in profitability, influenced by economic crises and market shocks such as the 2008 financial downturn and the COVID-19 pandemic. The linear regression model demonstrates a decent explanatory power with an R-squared value of 0.67, yet it fails to capture nonlinear patterns and sudden changes effectively. In contrast, the ANN model significantly improves forecasting accuracy, achieving an R-squared of 0.82 and a lower prediction error, highlighting the advantages of AI in modeling complex financial relationships. The findings underscore the transformative potential of integrating advanced data mining methods into accounting practices. AI-driven models enable proactive financial risk management, enhanced fraud detection, and improved audit quality. However, challenges remain concerning data quality, model interpretability, and the integration of AI within traditional accounting frameworks. The study suggests adopting explainable AI techniques and hybrid modeling approaches to balance accuracy with transparency. Furthermore, the digital transformation of financial reporting, the rise of fintech ecosystems, and innovations such as blockchain necessitate adaptive accounting methods supported by data mining and AI. As companies increasingly operate in dynamic and uncertain environments, leveraging these technologies is essential for accurate financial forecasting and robust corporate governance. In conclusion, this research highlights that while traditional models provide a useful baseline, the future of accounting lies in harnessing AI and data mining to enhance decision-making, optimize financial reporting, and sustain organizational resilience in an evolving economic landscape.